ANTOA`S RIDE ON SOCIAL CONSCIOUSNESS XPRESS - WILL, RALF G (IJRDO - Journal of Social Science and Humanities Research, 2024)
This article in my ANTOA series outlines analogy between my New Theory of Art, seen as journey, and a travel itinerary that includes train, plane and offroad vehicle. Starting out in Danish capitol of Copenhagen and arriving in north German metropole of Hamburg, the train stops at anthropoligcal, sociological and psychological stations. The journey continues via air to Johannesburg in South Africa. The experience is called Social Consciousness Xpress after title of essay published in 2015, calling visual artists to send samples of socially motivated works in an epoch of poor political leadership. The article explains how laypeople gained access to the myth of creativity. Especially the modern age popularizing the notion. Eg thru ethnological expeditions of expressionists like Emil Nolde and Max Pechstein, yet the message heavily coded and rarely appreciated by outsiders. It also illustrates link between stone-age processing of artefacts and their imaginative value, long overlooked and part of anthropological angle of creative travels. The article ends by quoting the 5-pointer table of the New Arts Theory as worthwhile final destination. The universal itinerary of soulful invention marked by detours into personality, social consciousness, skills innovation, abstraction and symbolic message. As cornerstones of and signposts to true Art.